Pengaruh Komunikasi Interpersonal Guru Terhadap Keaktifan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam - Indah Fajarwati; Akhmad Syahid; Surani Surani; Abdul Wahab (Universitas Muslim Indonesia, 2021)
This study aims to determine the interpersonal communication of PAI teachers at SMA Negeri 8 Makassar. The learning activity of PAI students at SMA Negeri 8 Makassar, as well as the influence of teacher interpersonal communication on the learning activities of PAI students at SMA Negeri 8 Makassar by using quantitative descriptive types. And the data analysis method is a simple linear regression with SPSS 25 program and the frequency percentage formula. The total population is 864 students, while the sample taken by the author is a random sample of 10% of the population, namely 86 respondents. Interpersonal communication of PAI teachers based on the perceptions of students, the total average of interpersonal communication of PAI teachers is 39.16, which means that the interpersonal communication of PAI teachers is in the high category and the learning activity of PAI students in SMA. Negeri 8 Makassar is a total of 64 questionnaires. ,35 means that based on the perceptions of students, active learning. PAI students are in the high category. The results of the analysis using simple linear analysis in the SPSS program show a simple regression formula which is known that the learning activity of students is influenced by 1,269 points of teacher interpersonal communication plus a constant value of 18,631. The other 3% is influenced by other variables.